The EU as an emerging coordinator in development cooperation: perspectives from sub-Saharan Africa - Delputte, Sarah (Afrika Focus, 2013)
This report presents the proceedings of the eld research conducted in the framework of a doctoral research on the European Union (EU) as an emerging coordinator in development cooperation. This research aims to seek in-depth and interpreted understanding of the paradox between the EU’s ambitions on the one hand and practice on the ground on the other by investigating the EU’s role in four sub-Saharan African countries (Tanzania, Zambia, Burkina Faso and Senegal). As such, it aims to add empirical evidence to the debate on the role of the EU as a development actor. More specifically, it investigates how the ambitions of the EU are translated at country level and in which situations the EU is more/less likely to act as a coordinator, making use of a pragmatist research approach. This approach is especially suited to problem-driven research that aims to understand a complex phenomenon. The article introduces the research question and the rationale, gives an overview of the research approach and the methodological considerations and ends with a summary of the research process and the preliminary findings of the eld research. Key words: EU development policy, aid effectiveness, coordination, pragmatism, interview research